Intra-abdominal fat is related to metabolic syndrome and non-alcoholic fat liver disease in obese youth - Silveira, Loreana Sanches [UNESP]; Monteiro, Paula Alves [UNESP]; Antunes, Bárbara de Moura Mello [UNESP]; Seraphim, Patrícia Monteiro [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Christofaro, Diego G Destro [UNESP]; Júnior, Ismael F Freitas [UNESP] (Springer Nature, 2013)
Background: Previous studies have shown an association between adiposity, especially intra-abdominal adipose tissue, and hemodynamic/metabolic comorbidities in adults, however it is not clear in pediatric population. The aim of the study was to analyze the relationship between non-alcoholic fatty liver disease (NAFLD) and components of metabolic syndrome (MS) with values of intra-abdominal (IAAT) and subcutaneous (SCAT) adipose tissue in obese children and adolescents.Methods: Cross-sectional study. Subjects: 182 obese sedentary children and adolescents (aged 6 to 16 y), identified by the body mass index (BMI). Measurements: Body composition and trunk fat by dual-energy X-ray absorptiometry- DXA; lipid profile, blood pressure and pubertal stage were also assessed. NAFLD was classified as absent (0), mild (1), moderate (2) and severe (3), and intra-abdominal and subcutaneous abdominal fat thickness were identified by ultrasound. The MS was identified according to the cut offs proposed by World Health Organization adapted for children and adolescents. The chi-square test was used to compare categorical variables, and the binary logistic regression indicated the magnitude of the associations adjusted by potential cofounders (sex, age, maturation, NAFLD and HOMA-IR).Results: Higher quartile of SCAT was associated with elevated blood pressure (p = 0.015), but not associated with NAFLD (p = 0.665). Higher IAAT was positively associated with increased dyslipidemia (p = 0.001), MS (p = 0.013) and NAFLD (p = 0.005). Intermediate (p = 0.007) and highest (p = 0.001) quartile of IAAT were also associated with dyslipidemia, independently of age, sex, maturation, NAFLD and HOMA-IR (homeostatic model assessment-insulin resistance).Conclusion: Obese children and adolescents, with higher IAAT are more prone to develop MS and NAFLD than those with higher values of SCAT, independent of possible confounding variables. © 2013 Silveira et al.; licensee BioMed Central Ltd.
Keywords: Adolescents; Children; Metabolic syndrome; Non-alcoholic fatty liver disease; Obesity; Trunk fat; insulin; adolescent; adolescent health; anthropometric parameters; blood pressure; body composition; child; comorbidity; cross-sectional study; dual energy X ray absorptiometry; dyslipidemia; echography; female; human; hyperinsulinemia; intraabdominal fat; major clinical study; male; metabolic syndrome X; nonalcoholic fatty liver; obesity; preschool child; puberty; risk assessment; school child; sedentary lifestyle; subcutaneous fat